2014
DOI: 10.1097/hnp.0000000000000041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Live Sax Music on Various Physiological Parameters, Pain Level, and Mood Level in Cancer Patients

Abstract: Live music performed with a saxophone could be introduced in oncology care to improve the oxygen saturation and mood in cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 67 publications
1
61
0
6
Order By: Relevance
“…The number of music sessions was 1–3 in the included studies and it did not affect cancer‐related pain of the patients in the included studies. It was found that the effect size was larger in the studies which applied three music sessions (Burrai et al, ). However, a single music session was found to be effective in cancer‐related pain (Huang et al, ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The number of music sessions was 1–3 in the included studies and it did not affect cancer‐related pain of the patients in the included studies. It was found that the effect size was larger in the studies which applied three music sessions (Burrai et al, ). However, a single music session was found to be effective in cancer‐related pain (Huang et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…It is thought that the small size of the sample group affected the results of the studies and that sample size resulted in a medium‐sized effect in the results of the meta‐analysis (Bigby, ). In three studies, it was found that music interventions were effective in reducing pain intensity (Arruda et al, ; Bilgiç & Acaroğlu, ; Huang et al, ), there was no statistically significant difference on pain intensity others studies (Bradt et al, ; Burrai et al, ; Toccafondi et al, ). In one study, it was thought that music intervention was not effective because it was applied to control and intervention groups (Bradt et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis also indicated the effectiveness of therapist‐provided music interventions in reducing the severity of anxiety and depression, with moderate to large effects being observed in cancer patients (Tsai et al, 2014). Other observed effects of MT during chemotherapy include relaxation (Burrai, Micheluzzi, & Bugani, 2014) and reduction of the treatment side effects (Moradian & Howell, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…137 In the holistic view of the human being, music can gain, sustain, or maintain this human dimension. 138 Music can yield positive experiences, a sense of wholeness and coherence, and can be linked to the patients' inner dimension: many pieces of music may speak directly to us recalling positive emotions and peace. 139 Within many societies, music is an integral part of life, 140 and this existential condition may provide resources for the recovery of self-identity.…”
Section: Discussionmentioning
confidence: 99%